2016
DOI: 10.3389/feart.2016.00093
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Sr and Nd Isotopic Ratios of Mineral Particles in Cryoconite in Western Greenland

Abstract: In order to better understand the source of minerals on the dark-colored ice, located in the Greenland ice sheet ablation zone, we analyzed the Sr and Nd isotopic ratios of minerals in cryoconite, which were collected from glaciers in northwest and southwest Greenland. We focused on the following: (i) comparison of the isotopes of minerals in cyroconite with those in sediments from local and distant areas, (ii) regional variations in western Greenland, and (iii) spatial variations across an individual a glacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…S7 in the supplements). Therefore, meltout is the main source of dust on the ice surface, which is also supported by a study of the isotopic composition (Nagatsuka and others, 2016).…”
Section: Meltout Of Impuritiesmentioning
confidence: 61%
“…S7 in the supplements). Therefore, meltout is the main source of dust on the ice surface, which is also supported by a study of the isotopic composition (Nagatsuka and others, 2016).…”
Section: Meltout Of Impuritiesmentioning
confidence: 61%
“…Previous studies reported that mineral dust on glaciers in northwestern and south-western Greenland is mainly supplied from local ground surfaces (e.g. moraine near the glacier) rather than the distant areas (Nagatsuka et al, , 2016. Therefore, the algal spores, which were washed out from the glacier and stayed on the ground, may be supplied with dust around the glacier by wind.…”
Section: Origin Of Snow Algae and Their Growth Condition On The Qaanamentioning
confidence: 99%
“…On all of the study glaciers, filamentous cyanobacteria genus Phormidesmis (mostly P. priestleyi) was abundant in all size fractions of granules. P. priestleyi has been isolated from Antarctic lake originally (Taton et al 2010), and has also been reported from many of Arctic glaciers (Chrismas et al 2016, Gokul et al 2016, Uetake et al 2016, Anesio et al 2017, Cameron et al 2017. Relative abundance and SIMPER similarity of this genus largely increased in larger than size 250, which Uetake et al (2016) pointed out as the distinct boundary of carbon ratio and species diversity in cryoconite granules (SI Table 3 Despite of the high abundance of this genus, 16S rRNA gene network analysis showed that abundance of P. priestleyi are poorly connected to other bacteria (Gokul et al 2016).…”
Section: : Cyanobacteria Characterizing Cryoconite Granulesmentioning
confidence: 99%
“…On the glacier surface, the size of cryoconite granules usually varied from μ m to mm in diameter, because filamentous cyanobacteria interweave their cells to make a granule and granule size is changed by degree of microbial growth. 16S rRNA gene amplicon sequencing of bacterial community in different granule size on a Greenland glacier revealed that the communities were distinctive among the size (diameter) of the granules and their diversity largely differed between granules of larger and smaller than 250 μm in diameter (Uetake et al 2016). However, this study was done on a single glacier and it is difficult to presume spatial variation of microbial communities with granule size changes, because microbial communities are quite different even in adjacent glaciers (Edward et al 2011, Lutz et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation